RELATIONSHIP BETWEEN FAMILY SUPPORT AND COMPLIANCE IN CONSUMPTION OF FEEL TABLETS IN FEMALE ADOLESCENTS AT SMA UNGGULAN BPPT DARUS SHOLAH JEMBER: Kesehatan Reproduksi Remaja - Evita, EVITA DIAN MARWATI; Ernawati Anggraeni (LPPM Universitas dr. Soebandi, 2024)
Background: Adolescents often experience anemia due to high iron requirements, so that iron deficiency in the body is quite severe. Based on data from RISKESDAS 2019, the achievement was only 1.4% of female adolescents who were compliant in consuming TTD according to the recommendation of 1x a week, while the other 98.6% of TTD consumption was still less than 52 tablets for one year. TTD is an effort to reduce the incidence of anemia in female adolescents, so family support is needed in compliance with consuming Fe tablets. Objective: To analyze the relationship between family support and compliance in consuming Fe tablets in female adolescents. Method: The population in this study were all female adolescents at SMA Unggulan BPPT Darus Sholah Jember totaling 147 respondents and a sample of 107 with a correlation design using a cross-sectional approach using the simple random sampling method, research instruments using questionnaires. Univariate analysis of frequency distribution and percentage, bivariate analysis used was the Chi-Square test. Results: The results obtained that family support for adolescent girls is in the good category and almost all adolescent girls are compliant in consuming Fe tablets, the results of statistical tests show a significant relationship between family support and compliance in consuming Fe tablets. Conclusion: Good family support will form adolescent girls who are compliant in consuming Fe tablets.